KEARIFAN TRADISIONAL PERLINDUNGAN DAN PEMANFAATAN SUMBERDAYA HUTAN OLEH SUKU KANUME DI TAMAN NASIONAL WASUR - Muhammad Budi Mulyawan; Sambas Basuni; Nandi Kosmaryandi (Media Konservasi, 2013)
Wasur National Park (TN Wasur), which is located in Merauke Papua, is one of 50 national parks in Indonesia. In the international scale, the TN Wasur are on track migratory birds from the northern hemisphere (Siberia, North China and Japan) to the southern hemisphere (Australia) or otherwise. TN Wasur is a place to stop and migration destination for migrant birds (Scolopacidae and Charadriidae), as well as the habitat of endemic birds, birds of the Trans-Fly (Indonesia-Papua New Guinea) and the marsupial animals (marsupials). The ethnic of Kanume is one of the indigenous communities who have long been living in TN Wasur, which has the largest region in Wasur, about 305.312 ha. The ethnic of Kanume has specific rules and traditional wisdom in managing lands of the ulayat. The ulayat lands are managed by the clans in the ethnic of Kanume. The results showed that the people of clans in the Kanume ethnic have a custom rules and wisdom in terms of protection and utilization of forest resources. Clans in the ethnic of  Kanume has ownership rights at the ulayat land to protect and exploit resources that there can be found sacred places, the old village, the well nature, hamlet of sago, and places the ancestral journey. In traditional wisdom and resource utilization, the ethnic of Kanume have a culture that supports the management of the forest resource. This can be seen by the existence of the Division of conception space based on the area of ulayat customs, the system of mastery and ownership of land, Sasi system and the belief of Totem (Totemism). Keywords: suku Kanume, Taman Nasional Wasur, traditional wisdom